Somatic survival and organ donation among brain-dead patients in the state of Qatar. Issue 1 (December 2016) - George, Saibu; Thomas, Merlin; Ibrahim, Wanis; Abdussalam, Ahmed; Chandra, Prem; Ali, Husain Shabbir; Raza, Tasleem
Abstract Background The Qatari law, as in many other countries, uses brain death as the main criteria for organ donation and cessation of medical support. By contrast, most of the public in Qatar do not agree with the limitation or withdrawal of medical care until the time of cardiac death. The current study aims to examine the duration of somatic survival after brain death, organ donation rate in brain-dead patients as well as review the underlying etiologies and level of support provided in the state of Qatar. Methods This is a retrospective study of all patients diagnosed with brain death over a 10-year period conducted at the largest tertiary center in Qatar (Hamad General Hospital). Results Among the 53 patients who were diagnosed with brain death during the study period, the median and mean somatic survivals of brain-dead patients in the current study were 3 and 4.5 days respectively. The most common etiology was intracranial hemorrhage (45.3%) followed by ischemic stroke (17%). Ischemic stroke patients had a median survival of 11 days. Organ donation was accepted by only two families (6.6%) of the 30 brain dead patients deemed suitable for organ donation. Conclusion The average somatic survival of brain-dead patients is less than one week irrespective of supportive measures provided. Organ donation rate was extremely low among brain-dead patients in Qatar. Improved public education may lead to significant improvement in resource utilization as well as organ transplant donors and should be a major target area of future health care policies.